Sludge Reduction Technologies in Wastewater Treatment Plants - Foladori, Paolo (IWA Publishing, 2010)
Sludge Reduction Technologies in Wastewater Treatment Plants is a review of the sludge reduction techniques integrated in wastewater treatment plants with detailed chapters on the most promising and most widespread techniques. The aim of the book is to update the international community on the current status of knowledge and techniques in the field of sludge reduction. It will provide a comprehensive understanding of the following issues in sludge reduction: principles of sludge reduction techniques; process configurations; potential performance; advantages and drawbacks; and economics and energy consumption. This book will be essential reading for managers and technical staff of wastewater treatment plants as well as graduate students and post-graduate specialists.